Missing in Action? France and the Politicization of Trade and Investment Agreements - Meunier, Sophie (2020)
Negotiations for the Transatlantic Trade and Investment Partnership (TTIP) between the European Union (EU) and the United States (US) and for the Comprehensive Economic and Trade Agreement (CETA) between the EU and Canada have provoked massive mobilization throughout Europe, both on the streets and online. Yet France, long at the epicenter of anti-globalization and anti-Americanism, has played a surprisingly modest role in the mobilization campaign against these agreements. This article asks why France did not contribute to anti-TTIP mobilization and, more broadly, how patterns of French mobilization over trade have changed over the past two decades. Using comparative-historical analysis, we explore to what extent this puzzling French reaction can be traced to changing attitudes towards the US, agenda-shaping by the French government, and transformations in the venues and techniques of social mobilization. We thus contribute to the growing literature on the politicization of trade agreements and offer insights into the links between domestic and international politics.